Volcanism on Io a comparison with Earth - Davies, Ashley Gerard 1961- (Cambridge planetary science, 2007)
The most powerful volcanoes in the Solar System are not on Earth, but on Io, a tiny moon of Jupiter. Whilst Earth and Io are the only bodies in the Solar System to have active, high-temperature volcanoes, those found on Io are larger, hotter, and more violent. This, the first book dedicated to volcanism on Io, contains the latest results from Galileo mission data analysis. As well as investigating the different styles and scales of volcanic activity on Io, it compares these volcanoes to their contemporaries on Earth. The book also provides a background to how volcanoes form and how they erupt, and explains quantitatively how remote-sensing data from spacecraft and telescopes are analysed to reveal the underlying volcanic processes. This richly illustrated book will be a fascinating reference for advanced undergraduates, graduate students and researchers in planetary sciences, volcanology, remote sensing and geology